STRATEGI PERENCANAAN PENDIDIKAN ISLAM DALAM PENINGKATAN MUTU PEMBELAJARAN DI MTS DARUL FALAH REMBUL - Muhamad Hamzah (STKIP Pesisir Selatan, 2025)
Thorough planning in every activity is an essential first step to optimally achieve educational goals, especially in the context of improving the quality of learning. This study aims to describe the Islamic education planning strategy in an effort to improve the quality of learning at MTs Darul Falah Rembul in the digital era. Using a qualitative approach with a case study design, data were obtained through participatory observation, in-depth interviews, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that the school has implemented systematic learning planning, including needs analysis, program development, and the selection of relevant methods and media. The integration of technology such as projectors, Google Classroom, WhatsApp Group, and other digital media has been proven to increase student interest, motivation, and understanding of Islamic Religious Education (PAI) materials. Teachers are encouraged to develop pedagogical competence and digital literacy through the implementation of innovative strategies such as the use of audiovisual media, group discussions, flipped classrooms, and blended learning. The implementation of these strategies results in a more interactive, contextual, and adaptive learning process to students' needs in the digital era.